Role of autoimmunity in primary biliary cirrhosis - Shi, Tian-Yan (Baishideng Publishing Group Co., Limited, 2012)
Primary biliary cirrhosis (PBC) is an autoimmune liver disease characterized by the presence of serum autoantibodies and chronic nonsuppurative destructive cholangitis. The pathogenesis of PBC involves environmental factors, genetic predisposition and loss of immune tolerance. In recent years, it has become univocally accepted that an inappropriately activated immune response is one of the most important factors in PBC. In this study, the role of autoimmunity in PBC is summarized and a feasible research orientation is recommended.